Outcomes of Cyclogest Pessary versus Conservative Treatment in Managing Threatened Miscarriage: A Comparative Analysis - Sanna Khan; Kanta Bai Ahuja; Bushra; Saira Saeed; Urooj Niazi; Fozia Shaikh, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Objective: This study aims to compare the effectiveness of Cyclogest pessary against conservative management in women experiencing Potential miscarriage or also referred to as threatened abortion, focusing on pregnancy continuation, maternal health outcomes, and neonatal results. Study design: A prospective cohort study Place and Duration: This study was conducted in, District Headquarter Hospital Mirpurkhas Pakistan from March 2024 to March 2025 Methodology: A prospective cohort design was employed. Participants were assigned to two groups based on the clinical management approach: The Cyclogest Group (n=100), which received a daily 400 mg dose of vaginal progesterone (Cyclogest pessary) until 20 weeks of pregnancy or symptom resolution; and the Conservative Management Group (n=70), where participants received alternate forms of progesterone (oral or intramuscular) for similar therapeutic purposes. The data was analyzed using the SPSS version 25, and the statistical significance was defined as p ≤ 0.05 and the software used descriptive statistics which set the baseline characteristics. Results: The average age for the Cyclogest group was 28.2 ± 5.1 years, and for the conservative group, it was 27.5 ± 5.4 years (p = 0.27). Both groups were similar in terms of gravidity, parity, and gestational age at the time of initial presentation (p > 0.05). Pregnancy continuation in the past 20 weeks was notably higher in the Cyclogest group (85%) compared to the conservative management group (75%), with a p-value of 0.005. The incidence of complete miscarriage was also lower in the Cyclogest group (12%) compared to the conservative group (28%). Maternal complications such as postpartum hemorrhage, infections, and hypertensive disorders showed no statistically significant differences between the two groups (p > 0.05). Conclusion: The use of Cyclogest pessary significantly enhances pregnancy continuation rates in women with Potential miscarriage or also referred to as threatened abortion compared to conservative management. Further randomized controlled trials are necessary to confirm these findings and refine clinical guidelines for treatment.